Integrating Lectora Inspire into Physics Learning: A Pathway to Enhance Critical and Creative Thinking Abilities through Interactive Learning Media - Januarizky, Rida; Rahim, Fanny Rahmatina; Sari, Silvi Yulia (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2024)
As a means for conveying knowledge to pupils, learning media is required in the learning process. However, teachers are not highly involved in the development of learning media. Some learning media generated by instructors in high schools in Padang do not match the criteria for good learning media. As a result, more study is required to create interactive learning media that meets quality media criteria. This study contains ADDIE model development research. Lectora Inspire was used to create the media. The media validity score was 0.76. This Picture shows that the developed media is appropriate. The media's practicability was 0.89. This number demonstrates that the media may be utilised in schools.